Alice Walker's Meridian and the Question of Just Violence - Šesnić, Jelena (2010)
At a time of growing interest in questions of ethics in contemporary theory, this article suggests a broader understanding and offers a historical perspective of the ethical implications which from the start have been presupposed in US ethnic literatures. Alice Walker’s Civil-Right’s Bildungsroman Meridian (1976), with its entangled implications relative to the issues of violence, revolution, social and personal transformation, is a case in point. These concerns potentially work at cross purposes, but the argument of this paper outlines the problematic possibility that some forms of violence, if ritualized, circumscribed and symbolized appropriately, as suggested by models of Freudian psychoanalysis (as outlined in Totem and Taboo), Julia Kristeva’s model of abjection, and René Girard’s sacrificial anthropology, offer modes of regarding violence as just, that is, responsive to ethical concerns. Such a redefinition of violence also takes place in conjunction with, rather than separate from, narrower aesthetic concerns, as proposed further by Elaine Scarry, Terry Eagleton and, again, Julia Kristeva, given their work at the intersection of ethics and symbolic forms.
Projekt MZOS
Projekt MZOS
ENG